Hollow silica particles from microemulsion - Jafelicci, M.; Davolos, Marian Rosaly [UNESP]; dos Santos, F. J.; de Andrade, S. J. (Elsevier B.V., 1999)
Silica particles were obtained by addition of diluted soluble sodium silicate in sodium 1,2 bis (2-ethylhexyloxycarbonyl)-1-ethenesulfonate reverse microemulsions, in which aqueous phase was nitric acid solution and the water/surfactant ratio (W) was 5 or 10. Products, whether washed or not, were dried at 100 degrees C and suspended in different solvents: heptane, water, kerosene or pentane for making SEM measurements. Thermal treatments of washed silica samples were carried out at 900 degrees C and 1200 degrees C. Silica particles of sizes from 1 to 10 mu m were obtained at room temperature without changing their shape due to thermal treatment and crystallization. SEM micrographs show hollow particles suggesting that silica preferably polymerizes on microemulsion droplet interface where ionic strength of nitric acid aqueous solution is favourable for silica polymerization reaction. (C) 1999 Elsevier B.V. B.V. All rights reserved.